PERAN GENDER DALAM MEMODERASI PENGARUH KEAMANAN TERHADAP MINAT GENERASI MILENIAL MENGGUNAKAN E-MONEY DI YOGYAKARTA - Elisa Ratna Kumalasari; Algifari (LPPM STIE YKPN Yogyakarta, 2024)
The aims of this study is to analyze the role gender to moderate in effect of security on interest using e-money in transactions by the millennial generation. This research was conducted in the province of DIY and respondents' perceptions of the ease and security using e-money for transacting were obtained from questionnaires was distributed in the period from October 4, 2021 to October 31, 2021. This study has involved 102 respondents and data was processed using SPSS to obtain the Macro Hayes model. This study obtained empirical e vidence that the perceptions of ease and security have a positive effect on interest of the millennial generation using e-money in the province of DIY. However, this research found no evidence that gender have moderating effect to perceptions security on interest by the millennial generation in using e-money. Keywords: Perception of Ease, Perception of Security, Interests, Millennial Generation, Macro Hayes Model.